Comprehensive Review “Literature Circle” Teaching and Learning Strategy in Adult Classroom Setting - Muhammad Asif ,; Kaleem Sarfaraz,; Burhanullah,; Suleman Jacob,; Sherullah,; Sabiha Asif, (Dialogue Social Science Review (DSSR), 2025)
This discussion paper consists of 21 research articles regarding literature circle learning strategy in adult classroom setting to find out the outcomes and effectiveness of literature circle learning strategy in adult classroom setting. Literature circle learning strategy is a small group discussion consists of six roles of the students in a circle to reading and comprehension in classroom setting. There is need of assess engagement of students in classroom students are anxious when teacher in classroom asks question from student regarding pre reading and post reading at the home. Students are not satisfied with conventional method of teaching and learning therefore new strategies regarding engagement of class is very necessary in classroom (Nawaz et al., 2024). Theory is useless without practice because the student is having funds of knowledge but teacher is a facilitator teacher should be having skills to engage the students in classroom like activities in classroom the retention of knowledge is increased with the teaching and learning with activates as compared to traditional and conventional strategies of teaching and learning in BSN education. (F Soomro et al., 2021). A cross sectional descriptive study was conducted in Dow University in nursing department to evaluating the academic performance of students and issues in Nursing education in public sectors. there were multiple problems regarding altered academic performance of students observed, one of those problems is the lack of interest in classroom learning. There should be conducted any interventional study regarding teaching and learning strategies (V Kumar et al., 2024). There are so many problems in academic performance in nursing education services it is scoping review of different 21 articles. According to author of this scoping review students of BSN education are weak in English language due to lack of environment therefore they need to create a circle for literary work in classroom to engagement in English literature. Study of book has been decreased in this period due to usages of AI to complete the assignments because students are not interested in reading deeply but they want to finish the degree program.(Davis et al., 2024). The qualitative research study was conducted in to detect the needs and gaps in teaching and learning strategy in classroom of BSN education. Interviews were conducted from students stated that students were satisfied in education with activities in classroom in which students can do something. Findings of study that students were not motivated without facilitation of teachers in classroom teacher should encourage to students in engagement in literary work in classroom. (S Alexander et al., 2024). There are 21 article review in this paper which consists of total 20 international papers and one Pakistani research paper. 36 articles were read but 21 were selected for literature review. Database google scholar, PubMed and scispace were used to searching the articles. Bullion operators “OR” and “And” were used to searching the articles. Most of research articles which were reviewed according to articles literature circle learning strategy is effective for teaching and learning in classroom and it is best for retention of knowledge among students in adult classroom. It is learner centered approach based on literary work in classroom. It is best for reading in a circle of students.